Peranan Koperasi dalam Peningkatan Minat Guru untuk Bergabung Kedalam Koperasi Karyawan Musthafawiyah Pondok Pesantren Musthafawiyah - Wahdini Wahdini; Andy Hakim; Muhlisah Lubis (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study was conducted on the basis of describing the Role of Cooperatives in Increasing Teachers' Interest in Joining the Musthafawiyah Employee Cooperative (Case Study of the Musthafawiyah Employee Cooperative of the Musthafawiyah Islamic Boarding School). This study was conducted from October 2023 to July 2024. The study used a phenomenological approach. The data validation technique was carried out by digging up information from several informants who were directly related to the cooperative. In addition, the researcher also conducted direct observations at the research location to verify the data whether the data obtained from the informants was in line with the reality in the field or not. The results of this study, the author concluded that the cooperative had not been able to carry out its role properly in increasing teachers' interest in joining and actively participating in the Musthafawiyah Employee Cooperative, as can be seen from the cooperative members who left the cooperative, the number of members did not increase every year. This is also referred to by several factors, namely individual factors and environmental factors. To overcome the lack of interest of teachers to join the Musthafawiyah employee cooperative, namely by increasing socialization and communication, strengthening the role of leadership, providing incentives and ease of joining, improving the quality of cooperative services, and creating synergy with related institutions.